The economists' hour : false prophets, free markets, and the fracture of society - Appelbaum, Binyamin (Little, Brown and Company, 2019)
Before the 1960s, American politicians had never paid much attention to economists. But as the post-World War II boom began to sputter, economists gained influence and power - first in the United States and then around the world as their ideas inspired nations to curb government, unleash corporations, and hasten globalization. Milton Friedman's libertarian ideals, Arthur Laffer's supply-side economics and Paul Volcker's austere campaign against inflation all left a profound mark on American life. So did lesser-known figures like Walter Oi, a blind economist whose calculations influenced President Nixon's decision to end military conscription; Alfred Kahn, who deregulated air travel; and Thomas Schelling, who put a dollar value on human life. The economists promised steady growth and broadly-shared prosperity, but they failed to deliver. Instead, the single-minded embrace of markets has come at the expense of soaring economic inequality, the faltering health of liberal democracy, and the prospects of future generations.